2008
DOI: 10.1016/j.jtcvs.2007.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Hemidiaphragm plication after repair of congenital heart defects in children: Quantitative return of diaphragm function over time

Abstract: Hemidiaphragm paresis results in significant morbidity after repair of congenital heart defects. Early diagnosis and plication result in timely extubation. The plicated diaphragm demonstrates return of function that may improve over time. This is the first study to numerically quantitate the degree of diaphragm recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 15 publications
0
32
0
2
Order By: Relevance
“…This is not surprising, given that the phrenic nerve injury during cardiac surgery leading to DP has a significant impact on respiratory mechanics in newborns and infants in particular. 11 The higher chest wall compliance in these patients results in a lower functional reserve volume. When paretic or parlayzed, the diaphragm sits higher and reduces lung volume and expansion on that side.…”
Section: Discussionmentioning
confidence: 98%
“…This is not surprising, given that the phrenic nerve injury during cardiac surgery leading to DP has a significant impact on respiratory mechanics in newborns and infants in particular. 11 The higher chest wall compliance in these patients results in a lower functional reserve volume. When paretic or parlayzed, the diaphragm sits higher and reduces lung volume and expansion on that side.…”
Section: Discussionmentioning
confidence: 98%
“…We, as many others, advocate for an early intervention, especially in neonates. In neonates and young children with little accessory muscle reserve, early surgical intervention facilitates the weaning process from mechanical ventilation, minimizing the risk for potential ventilator associated pneumonia and decreasing ICU and hospital length of stay 4,9–11 …”
Section: Discussionmentioning
confidence: 99%
“…Smith et al in a recent study has shown that both the plicatedand non plicated patients regain function at similar frequency (60% and 54.8% respectively) following a follow up period from 6 days to 17 years (17) . In a review of 46 patients who had undergone diaphragm plication following cardiac surgery Baker et al have numerically quantitated and demonstrated the return of function with a trend toward improvement over time (18) . Bilateral diaphragmatic paralysis occurs with much less frequency compared to unilateral DP, but affected patients usually do not tolerate ventilator weaning due to severe reduction in lung capacity.…”
Section: Discussionmentioning
confidence: 99%